2021
DOI: 10.1111/clr.13723
|View full text |Cite
|
Sign up to set email alerts
|

Delphi Project on the trends in Implant Dentistry in the COVID‐19 era: Perspectives from Latin America

Abstract: Aim To establish trends in Implant Dentistry in Latin America in the COVID‐19 pandemic. Material and methods A steering committee and an advisory group of experts in Implant Dentistry were selected among eighteen countries. An open‐ended questionnaire by Delphi methodology was validated including 64 questions, divided in 7 topics, concerning the various trends in dental implantology. The survey was conducted in two rounds, which provided the participants in the second r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Fifty-two Delphi studies were assessed as per the inclusion criteria, and 34 (67.3%) studies[ 24 - 57 ], were finally analyzed using nine evaluation points (Table 1 ). The data on medical specialty, geographical location, the purpose of the study, conclusion format, number of experts, and Delphi rounds were collected for each study (Table 2 ).…”
Section: Evaluation Of Recent Delphi Studiesmentioning
confidence: 99%
“…Fifty-two Delphi studies were assessed as per the inclusion criteria, and 34 (67.3%) studies[ 24 - 57 ], were finally analyzed using nine evaluation points (Table 1 ). The data on medical specialty, geographical location, the purpose of the study, conclusion format, number of experts, and Delphi rounds were collected for each study (Table 2 ).…”
Section: Evaluation Of Recent Delphi Studiesmentioning
confidence: 99%
“…Among the tested methods to achieve agreement on selecting a potential core set of outcomes, the Delphi methodology has become popular, even though Delphi‐based studies must be of sufficient quality to be considered valid (Sinha et al, 2011). In fact, Delphi methodology is progressively spreading in scientific publications in the different medical specialities (Carter et al, 2021; Millward et al, 2022; Mitchell et al, 2022; Munblit et al, 2022; Prorok et al, 2022; Rosala‐Hallas et al, 2022) and also in dentistry (Alarcón, Sanz‐Sánchez, López‐Pacheco, et al, 2021; Alarcón, Sanz‐Sánchez, Shibli, et al, 2021; Sanz et al, 2019). This is partially due to the ability of the Delphi method to distil relevant problems where knowledge is unclear, and by applying a structured process of gathering information from experts and other stakeholders through subjective‐intuitive foresight thinking, a final agreement is reached.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study was published, endorsed by FIPP and the Peruvian Association of Oral Implantology, evaluating the trends in Implant Dentistry during the COVID‐19 pandemic, in LatAm. The results showed that the biosafety protocols to minimize the risk of SARS‐CoV‐2 transmission are reliable, as well as the importance of the use of simulation and virtual reality technology in dental training 18 …”
Section: Introductionmentioning
confidence: 98%
“…The results showed that the biosafety protocols to minimize the risk of SARS-CoV-2 transmission are reliable, as well as the importance of the use of simulation and virtual reality technology in dental training. 18 The aim of the present study, endorsed by FIPP, was to assess, following the Delphi methodology, trends in the epidemiology, prevention, diagnosis, treatment and supportive care of periodontal diseases and education in LatAm, by the year 2030.…”
Section: Introductionmentioning
confidence: 99%